EPOC Substrate Metabolism AT/RT - Bryant, Tyler (My University, 2025)
Excess post-exercise oxygen consumption (EPOC) represents the elevated oxygen intake following physical activity as the body restores itself to resting state, and it is influenced by both the intensity and modality of exercise. While EPOC has been well-documented, its role in substrate metabolism—particularly the differential utilization of fats and carbohydrates post-exercise—warrants further investigation. This study examines EPOC and substrate metabolism following distinct bouts of aerobic and resistance exercise in untrained individuals, aiming to compare the metabolic outcomes associated with each mode of training. Participants completed randomized sessions of aerobic and resistance exercise, with metabolic variables including oxygen consumption (VO₂), respiratory exchange ratio (RER), and resting energy expenditure (REE) measured before, during, and after exercise using indirect calorimetry. The findings are expected to contribute to the growing body of literature on how different forms of exercise affect energy expenditure and fuel usage during recovery, with implications for weight management and metabolic health interventions. Previous studies have shown that resistance exercise often leads to a prolonged EPOC with a greater reliance on lipid oxidation, while aerobic activity may induce shorter, yet immediate changes in metabolism (Borsheim & Bahr, 2003; Lyons et al., 2006). Understanding these distinctions is particularly relevant for developing targeted exercise prescriptions, especially in sedentary or metabolically compromised populations. This research will inform practitioners and exercise scientists of the practical metabolic outcomes of aerobic versus resistance training, potentially influencing exercise program design for health and performance goals
Keywords: EPOC, metabolism, substrate